MODEL REGULATION OF THIRD-PARTY FUNDING IN INDONESIA: A COMPARATIVE STUDY - Kanris, Jesslyn; Amalia, Prita (Transnational Business Law Journal, 2020)
ABSTRACTThe emerging practice of third-party funding provides an answer for the party whose rights has been breached but are financially constrained to bring forth its claims to an investment arbitration. However, the practice of third-party funding does not always run smoothly according to its optimistic expectations and noble goals. The lack of concrete regulations regarding its practice imposes several issues concerning its involvement in investment arbitration. By using normative legal and case analysis approach, this paper analyses legal doctrines and principles in investment arbitration law and their implementations in the community through comparative cases. The research uses a descriptive analytical method which describes the applicable legal regulations correlated with legal theories and their implementation in the research object. The research was conducted by finding secondary data using primary, secondary, and tertiary legal materials. The results of the research show that the regulations regarding the practice of third-party funding in addition to provide access to justice for financially constrained parties is also required to provide answers to concerns raised by its involvement in investment arbitration. The action that can be done by the Indonesian government to solve the aforementioned problem is to issue a specific international arbitration law which includes the regulations regarding the practice of third-party funding.Keywords: Third-Party Funding in International Investment Arbitration, Indonesian Arbitration Law, Model Implementation of Indonesian International Arbitration Law.